Evaluation of the Quality of Governance in African Countries Using Aggregate Indicators - Novotná, Zuzana; Å ánová, Petra; Laputková, Adriana (International Journal of Economics and Financial Issues, 2016)
The paper focuses on evaluation of the quality of governance in 53 African countries. The quality of governance is evaluated using factors such as Government Effectiveness, Control of Corruption, Rule of Law, which are monitored in each African country individually for the period between 2004 and 2010. In order to assess the quality of governance as well as the relative position of each African country, the ratio aggregation method was used in its simple form. The results of the analysis show substantial disparities among African countries. Somalia, Zimbabwe and Equatorial Guinea reach the worst results, with considerably high levels of corruption. The results of the analysis of each country are presented using a coloured map of Africa. Keywords: Quality of Governance, Government Effectiveness, Control of Corruption, Rule of Law, Africa, aggregate indicator, ratio method. JEL Classifications: H75, K00